Assessment of essential surgical and anaesthesia care capacity: a cross-sectional study in five Pacific Island CountriesResearch in context - Rennie X. Qin; Grace Zhang; Meghan X. Lim; Ifereimi Waqainabete; Jemesa Tudravu; Josese Turagava; Rajeev Patel; Lisiate Ulufonua; Josephine Herman; Deacon Teapa; Yin Yin May; Margaret Tarere-Lehi; et al. (Elsevier, 2023)
Summary: Background: Pacific Island Countries (PICs) face unique challenges in providing surgical care. We assessed the surgical care capacity of five PICs to inform the development of National Surgical, Obstetric and Anaesthesia Plans (NSOAP). Methods: We conducted a cross-sectional survey of 26 facilities in Fiji, Tonga, Vanuatu, Cook Islands, and Palau using the World Health Organization - Program in Global Surgery and Social Change Surgical Assessment Tool. Findings: Eight referral and 18 first-level hospitals containing 39 functioning operating theatres, 41 post-anaesthesia care beds, and 44 intensive care unit beds served a population of 1,321,000 across the five countries. Most facilities had uninterrupted access to electricity, water, internet, and oxygen. However, CT was only available in 2/8 referral hospitals, MRI in 1/8, and timely blood transfusions in 4/8. The surgical, obstetric, and anaesthetist specialist density per 100,000 people was the highest in Palau (49.7), followed by Cook Islands (22.9), Tonga (9.9), Fiji (7.1), and Vanuatu (5.0). There were four radiologists and 3.5 pathologists across the five countries. Surgical volume per 100,000 people was the lowest in Vanuatu (860), followed by Fiji (2,247), Tonga (2,864), Cook Islands (6,747), and Palau (8,606). The in-hospital peri-operative mortality rate (POMR) was prospectively monitored in Tonga and Cook Islands but retrospectively measured in other countries. POMR was below 1% in all five countries. Interpretation: Whilst PICs share common challenges in providing specialised tertiary services, there is substantial diversity between the countries. Strategies to strengthen surgical systems should incorporate both local contextualisation within each PIC and regional collaboration between PICs. Funding: None.